2006
DOI: 10.1021/ja0525859
|View full text |Cite
|
Sign up to set email alerts
|

Origins of Stereoselectivity in Diels−Alder Cycloadditions Catalyzed by Chiral Imidazolidinones

Abstract: B3LYP/6-31G(d) density functional theory has been used to study Diels-Alder reactions of cyclopentadiene with α,β-unsaturated aldehydes and ketones organocatalyzed by MacMillan's chiral imidazolidinones. Preferred conformations of transition structures and reaction intermediates have been located. The dramatically different reactivities and enantioselectivities exhibited by two similar chiral imidazolidinones are rationalized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
59
0
9

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(76 citation statements)
references
References 52 publications
8
59
0
9
Order By: Relevance
“…Nach rechnerischen Untersuchungen durch Houk und Gordillo sind die Aktivierungsenergien für diese Lewis-Base-katalysierten DielsAlder-Reaktionen um 11-13 kcal mol À1 niedriger als für die entsprechenden thermischen Reaktionen. [161,162] Ganz ähnlich wie bei vielen anderen Lewis-Base-katalysierten Reaktionen wird die verstärkte Elektrophilie der Lewis-Base-katalysierten Diels-Alder-Reaktionen durch sehr ähnliche Prozesse ergänzt, bei denen die verstärkte Nucleophilie eine wichtige Rolle spielt. Bei der Umsetzung eines a,b-ungesättigten Ketons mit einem sekundären Amin kann das zunächst gebildete Iminiumion durch Protonentransfer in ein konjugiertes Enamin XLV überführt werden, das als Dien Diels-Alder-Reaktionen eingehen kann [Gl.…”
Section: Phosphankatalysierte Cycloadditionenunclassified
“…Nach rechnerischen Untersuchungen durch Houk und Gordillo sind die Aktivierungsenergien für diese Lewis-Base-katalysierten DielsAlder-Reaktionen um 11-13 kcal mol À1 niedriger als für die entsprechenden thermischen Reaktionen. [161,162] Ganz ähnlich wie bei vielen anderen Lewis-Base-katalysierten Reaktionen wird die verstärkte Elektrophilie der Lewis-Base-katalysierten Diels-Alder-Reaktionen durch sehr ähnliche Prozesse ergänzt, bei denen die verstärkte Nucleophilie eine wichtige Rolle spielt. Bei der Umsetzung eines a,b-ungesättigten Ketons mit einem sekundären Amin kann das zunächst gebildete Iminiumion durch Protonentransfer in ein konjugiertes Enamin XLV überführt werden, das als Dien Diels-Alder-Reaktionen eingehen kann [Gl.…”
Section: Phosphankatalysierte Cycloadditionenunclassified
“…[124] Houk and Gordillo [125,126] used B3LYP DFT to explore the amine catalyzed Diels-Alder cycloadditions of cyclopentadiene with a variety of a,b-unsaturated aldehydes and ketones (Scheme 20). Previous studies out of the Houk group had demonstrated that DFT can be a powerful tool to predict enantioselectivities observed experimentally in a variety of asymmetric organocatalyzed reactions.…”
Section: Organocatalysis Of Diels-alder Reactions With Chiral Imidazomentioning
confidence: 99%
“…Predicted selectivities are in excellent agreement with experiment. [125] 4.4 Catalysis of 1,3-Dipolar Cycloaddition Reactions…”
Section: Organocatalysis Of Diels-alder Reactions With Chiral Imidazomentioning
confidence: 99%
“…[ [65] Während die Oxazolidinone II und IV, die Aldehyde sehr gut als Iminiumionen aktivieren, bei diesen Reaktionen nahezu keinen Umsatz ergaben, eröffnete der Katalysator VI einen enantioselektiven Zugang zu substituierten Cyclohexylketonen.…”
Section: Macmillans Imidazolidinon-katalysatorenunclassified